Glass fiber filling reinforced high-pressure flame-retardant nylon material and preparation method thereof

By using PA6 resin, long carbon chain nylon resin, glass fiber, composite flame retardant and antioxidant in glass fiber filling reinforced flame retardant nylon materials, combined with the preparation method of twin screw extrusion mechanism, the problem of degradation of the material's performance and insufficient flame retardant in wet state is solved, and the balanced improvement of mechanical properties, flame retardant and electrical properties is achieved, and it is suitable for high-voltage automotive electrical products.

CN119592059APending Publication Date: 2025-03-11HUBEI HEJU POLYMER MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411918742.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing glass fiber filled reinforced flame retardant nylon materials have reduced mechanical and electrical properties in wet states, and their flame retardancy is not high, which affects the electrical properties after adding flame retardant.

Method used

Using a combination of PA6 resin, long carbon chain nylon resin, glass fiber, composite flame retardant and antioxidant, a nylon material with good mechanical properties, flame retardant and electrical properties is prepared through a twin-screw extrusion mechanism to control the processing temperature and rotation speed.

Benefits of technology

It achieves the balanced improvement of the mechanical properties, flame retardant properties and electrical properties of the material, and is suitable for high-voltage series of automotive electrical appliances that are high-strength, high-voltage resistant, halogen-free flame retardant.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005207430570000041
    Figure BDA0005207430570000041
  • Figure BDA0005207430570000051
    Figure BDA0005207430570000051
  • Figure BDA0005207430570000052
    Figure BDA0005207430570000052
Patent Text Reader

Abstract

The invention discloses a glass fiber filled and reinforced high-pressure flame-retardant nylon material and a preparation method thereof, and the glass fiber filled and reinforced high-pressure flame-retardant nylon material comprises the following components by weight: 30%-60% of PA6 resin, 15%-35% of long carbon chain nylon resin, 10%-30% of glass fiber, 15%-25% of a compound flame retardant, and 0.5%-2% of an antioxidant. The nylon material has the advantages of favorable mechanical properties, favorable flame retardancy, higher tracking index and balanced mechanical properties, flame retardancy and electrical properties, and can be used in high-voltage series products of automotive electrical appliances, which require high strength, high voltage resistance and halogen-free flame retardancy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a glass fiber filled reinforced high pressure flame retardant nylon material and a preparation method thereof. Background Art

[0002] As automobiles transform from traditional fuel vehicles to new energy vehicles, the operating environment of vehicles is quite different from that of traditional fuel vehicles, and the requirements for parts have also undergone a series of changes. Glass fiber-filled reinforced flame-retardant nylon materials are increasingly used in new energy vehicles, especially high-voltage series products. Due to the disadvantage of high water absorption of polyamide materials, the mechanical properties in wet state are greatly reduced, and the electrical properties in wet state are also greatly reduced; nylon itself is not highly flame-retardant. To obtain excellent flame retardancy, adding various flame retardants for flame retardant modification will affect its electrical properties. Therefore, it is necessary to develop glass fiber-filled reinforced high-pressure flame-retardant nylon materials with high CTI, excellent flame retardant properties and physical properties. Summary of the invention

[0003] Based on the deficiencies in the prior art, the purpose of the present invention is to provide a glass fiber filled reinforced high-voltage flame retardant nylon material and a preparation method thereof. The nylon material has good mechanical properties, good flame retardant properties, a high tracking index, and balanced mechanical properties, flame retardant properties, and electrical properties. It can be used in automotive electrical high-voltage series products that require high strength, high voltage resistance, and halogen-free flame retardancy.

[0004] In order to achieve the above purpose, this application adopts the following technical solutions:

[0005] In the first aspect, the present invention provides a glass fiber filled reinforced high-pressure flame retardant nylon material, which comprises the following components by weight percentage: 30%-60% PA6 resin, 15%-35% long carbon chain nylon resin, 10%-30% glass fiber, 15%-25% compound flame retardant, and 0.5%-2% antioxidant.

[0006] In the above technical solution, the PA6 resin is a medium-viscosity PA6 resin with a relative viscosity of 2.0 to 3.0.

[0007] In the above technical solution, the long carbon chain nylon resin is any one or a combination of PA1010, PA1012, PA12, and PA11.

[0008] In the above technical solution, the glass fiber is a chopped glass fiber treated with surface silane.

[0009] In the above technical solution, the compound flame retardant is a flame retardant masterbatch prepared by mixing diethyl aluminum hypophosphite flame retardant and modified hollow glass microspheres in a mass ratio of 2:1.

[0010] In the above technical scheme, the preparation method of the modified hollow glass microspheres is: adding a certain amount of hollow glass microspheres to a sodium hydroxide solution of a certain concentration, stirring, filtering, washing with acetic acid and deionized water, and drying in a vacuum drying oven, adding the dried hollow glass microspheres to an ethanol-water mixed solution containing a KH550 silane coupling agent, stirring, filtering, separating, and drying in a vacuum oven to obtain the modified hollow glass microspheres.

[0011] In the above technical solution, the antioxidant is any one or a combination of copper salt antioxidants H318 and H320.

[0012] In a second aspect, the present invention provides a method for preparing the above-mentioned nylon material, comprising the following steps:

[0013] S1: drying the PA6 resin, long carbon chain nylon resin, glass fiber, compound flame retardant and antioxidant;

[0014] S2: premixing the dried PA6 resin, long carbon chain nylon resin and antioxidant to obtain an initial mixture;

[0015] S3: The initial mixture is fed into the main feeder hopper of a twin-screw extruder, and conveyed by its own gravity and the main feeder screw. At the same time, the dried glass fiber and compound flame retardant are added to the side feeder hopper, and conveyed to the screw cavity of the twin-screw extruder through the side feeder screw. After heating, melting, extrusion and granulation by heating the barrel and screw shearing, the nylon material is obtained.

[0016] In the above technical solution, the processing temperature of the twin-screw extruder is controlled at 210-250° C., and the main engine speed is 300-350 rpm.

[0017] The beneficial effects of the present invention are as follows: the present invention adds a long carbon chain nylon resin with lower water absorption rate to the PA6 resin, improves the water absorption of the composite material, reduces the generation of polymer carbon channels when electrical breakdown occurs, and thus improves the electrical insulation performance of the material; by using surface-modified glass fiber for reinforcement modification, the glass fiber can be evenly dispersed in the resin, improves the interface compatibility between the resin and the glass fiber, and improves the mechanical properties; the compounded flame retardant has good dispersibility in the resin, the burning carbon layer migrates to the surface of the resin carbon layer, and the two combine to form a denser carbon layer, which is more conducive to blocking the heat conduction between the polymer and the heat source. After the flame retardant is compounded, the small amount of addition also reduces the influence of the flame retardant on the mechanical properties. Due to its spherical structure, the hollow glass microspheres can block the formation of carbon channels when the flame retardant is carbonized, thereby improving the electrical insulation performance of the material. The metal copper ions in the copper salt antioxidant react with alkyl or alkoxy free radicals through single-electron oxidation or reduction reactions to generate non-radical products, thereby cutting off the chain reaction cycle of thermal oxidation aging, thereby improving the thermal oxidation resistance of the material. DETAILED DESCRIPTION

[0018] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. The present invention can be implemented in many different forms and should not be construed as being limited to the embodiments set forth herein. On the contrary, these embodiments are provided so that this disclosure will be thorough and complete, and the concept of the present invention will be fully conveyed to those skilled in the art, and the present invention will only be limited by the claims.

[0019] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0020] The invention provides a glass fiber filled reinforced high-pressure flame retardant nylon material, which comprises the following components by weight percentage: 30%-60% of PA6 resin, 15%-35% of long carbon chain nylon resin, 10%-30% of glass fiber, 15%-25% of compound flame retardant, and 0.5%-2% of antioxidant.

[0021] PA6 resin is a medium-viscosity PA6 resin with a relative viscosity of 2.0 to 3.0.

[0022] The long carbon chain nylon resin is any one or a combination of PA1010, PA1012, PA12 and PA11.

[0023] The glass fiber is chopped glass fiber with surface treated with silane.

[0024] The compound flame retardant is a flame retardant masterbatch prepared by mixing diethyl aluminum hypophosphite flame retardant and modified hollow glass microspheres in a mass ratio of 2:1. The preparation method of the modified hollow glass microspheres is as follows: adding a certain amount of hollow glass microspheres to a sodium hydroxide solution of a certain concentration, stirring, filtering, washing with acetic acid and deionized water, and drying in a vacuum drying oven, adding the dried hollow glass microspheres to an ethanol-water mixed solution containing a KH550 silane coupling agent, stirring, filtering, separating, and drying in a vacuum oven to obtain the modified hollow glass microspheres.

[0025] The antioxidant is any one or a combination of copper salt antioxidants H318 and H320.

[0026] The present invention also provides a method for preparing a glass fiber filled reinforced high pressure flame retardant nylon material, comprising the following steps:

[0027] S1: drying PA6 resin, long carbon chain nylon resin, glass fiber, compound flame retardant and antioxidant (100°C, 4h);

[0028] S2: premixing the dried PA6 resin, the long carbon chain nylon resin and the antioxidant to obtain an initial mixture;

[0029] S3: The initial mixture is put into the main feeder hopper of the twin-screw extruder, and is transported by its own gravity and the main feeder screw. At the same time, the dried glass fiber and the compound flame retardant are added to the side feeder hopper, and are transported to the screw cavity of the twin-screw extruder by the side feeder screw. After heating and melting by the heating barrel and screw shearing, and extrusion granulation, the nylon material of the present invention is obtained.

[0030] Among them, the processing temperature of the twin-screw extruder is controlled at 210-250°C, and the main engine speed is

[0031] 300~350rpm.

[0032] The glass fiber filled reinforced high pressure flame retardant nylon material and preparation method of the present application will be described in detail below in combination with embodiments, comparative examples and experimental data.

[0033] Examples 1-3 and Comparative Examples 1-3

[0034] Sources of components in each embodiment and comparative example:

[0035] PA6 resin: Ningxia Ruitai Technology Co., Ltd., YN2700.

[0036] Long carbon chain nylon resin: DuPont, USA, PA10 brand: RSLC1600 NC010.

[0037] Glass fiber: chopped glass fiber treated with surface silane. Glass fiber: Jushi Group Co., Ltd., ECS10-03-568HD. The treatment method is: dissolve 20mL of KH550 silane coupling agent in 980mL of anhydrous ethanol to prepare a silane coupling agent solution with a volume fraction of 2%; add 10% mass fraction of glass fiber to the silane coupling agent solution, stir at 80-100℃ for 4-6h, filter out, put into a vacuum drying oven at 80-100℃ for drying and cooling, and obtain glass fiber treated with surface silane.

[0038] Compound flame retardant: The flame retardant masterbatch is prepared by mixing diethyl aluminum hypophosphite flame retardant and modified hollow glass microspheres in a mass ratio of 2:1. The preparation method of the modified hollow glass microspheres is as follows: adding a certain amount of hollow glass microspheres to a sodium hydroxide solution of a certain concentration, stirring, filtering, washing with acetic acid and deionized water, and drying in a vacuum drying oven, adding the dried hollow glass microspheres to an ethanol-water mixed solution containing a KH550 silane coupling agent, stirring, filtering, separating, and drying in a vacuum oven to obtain the modified hollow glass microspheres.

[0039] Diethyl aluminum hypophosphite flame retardant: Shandong Xiucheng Chemical Co., Ltd., ADP.

[0040] Hollow glass microspheres: 3M China Co., Ltd., S28HS.

[0041] Antioxidant: Brüggemann Chemical Co., Ltd., H320.

[0042] The preparation method of the nylon material of Examples 1-3 and Comparative Examples 1-3 comprises the following steps:

[0043] (1) Accurately weigh each component

[0044] The formulas of each embodiment and comparative example are as follows:

[0045]

[0046]

[0047] (2) premixing the PA6 resin, the long carbon chain nylon resin and the antioxidant after drying (100° C., 4 h) to obtain an initial mixture;

[0048] (3) The initial mixture is put into the main hopper of the twin-screw extruder, and conveyed by its own gravity and the screw of the first feeding zone of the extruder. At the same time, the treated glass fiber and the compound flame retardant are added to the hopper of the side feeder, and conveyed to the screw cavity of the extruder through the screw of the side feeder. After heating and melting by the heating barrel and screw shearing, extrusion and granulation, the nylon materials of Examples 1-3 and Comparative Examples 1-3 are finally obtained. The processing temperature of the twin-screw extruder is controlled at 210-250°C, and the main engine speed is 300-350rpm.

[0049] The materials obtained in Examples 1-3 and Comparative Examples 1-3 were tested for performance, and the test results are shown in the following table:

[0050]

[0051] As can be seen from the above table, in Examples 1 to 3 of the present invention, glass fiber-filled reinforced high-voltage flame-retardant nylon materials are developed by using different proportions of PA6 resin, long carbon chain resin, glass fiber, compounded flame retardant, and antioxidant. Compared with PA6 resin, long carbon chain nylon resin has a lower water absorption rate due to the lower concentration of amide groups in its molecules. Therefore, by compounding long carbon chain nylon with lower water absorption in PA6 resin, due to the presence of a certain proportion of long carbon chain nylon in the composite material, the electrical insulation performance of the material is improved by reducing the generation of polymer carbon channels when electrical breakdown occurs. The surface-treated glass fiber plays a reinforcing role and improves the mechanical properties of the composite material. By compounding hollow glass microspheres with diethyl aluminum hypophosphite flame retardant, the dense carbon layer formed can block the heat conduction between the polymer and the heat source, effectively improving the flame retardancy of the composite material; the hollow glass microspheres with spherical structure can hinder the generation of polymer carbon channels that cause electrical breakdown when the flame retardant is carbonized, thereby improving the electrical insulation performance of the material. Compound flame retardants can also reduce the overall addition amount of flame retardants, reducing the negative impact of flame retardants on the mechanical properties and electrical properties of materials. Copper salt antioxidants have excellent high-temperature protection and long-term protection, and can effectively avoid the decomposition and carbonization of materials during processing, thereby improving the antioxidant properties of the composition during processing and the anti-aging properties during use. The glass fiber-filled reinforced high-pressure flame-retardant nylon material of the present invention has good mechanical properties, good flame retardant properties, a high tracking index, and balanced mechanical properties, flame retardant properties, and electrical properties. It can be used in automotive electrical high-voltage series products that require high strength, high voltage resistance, and halogen-free flame retardancy.

[0052] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A glass fiber filled reinforced high pressure flame retardant nylon material, characterized by: Calculated by weight percentage, the composition includes: 30%-60% PA6 resin, 15%-35% long carbon chain nylon resin, 10%-30% glass fiber, 15%-25% compound flame retardant, and 0.5%-2% antioxidant.

2. The nylon material according to claim 1, characterized in that: The PA6 resin is a medium-viscosity PA6 resin with a relative viscosity of 2.0 to 3.

0.

3. The nylon material according to claim 1, characterized in that: The long carbon chain nylon resin is any one or a combination of PA1010, PA1012, PA12 and PA11.

4. The nylon material according to claim 1, characterized in that: The glass fibers are chopped glass fibers with surface silane treatment.

5. The nylon material according to claim 1, characterized in that: The compound flame retardant is a flame retardant masterbatch prepared by mixing diethyl aluminum hypophosphite flame retardant and modified hollow glass microspheres in a mass ratio of 2:

1.

6. The nylon material according to claim 5, characterized in that: The preparation method of the modified hollow glass microspheres is as follows: adding a certain amount of hollow glass microspheres to a sodium hydroxide solution of a certain concentration, stirring, filtering, washing with acetic acid and deionized water, and drying in a vacuum drying oven; adding the dried hollow glass microspheres to an ethanol-water mixed solution containing a KH550 silane coupling agent, stirring, filtering, separating, and drying in a vacuum oven to obtain the modified hollow glass microspheres.

7. The nylon material according to claim 1, characterized in that: The antioxidant is any one or a combination of copper salt antioxidants H318 and H320.

8. The method for preparing the nylon material according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1: drying the PA6 resin, long carbon chain nylon resin, glass fiber, compound flame retardant and antioxidant; S2: premixing the dried PA6 resin, long carbon chain nylon resin and antioxidant to obtain an initial mixture; S3: The initial mixture is fed into the main feeder hopper of a twin-screw extruder, and conveyed by its own gravity and the main feeder screw. At the same time, the dried glass fiber and compound flame retardant are added to the side feeder hopper, and conveyed to the screw cavity of the twin-screw extruder through the side feeder screw. After heating, melting, extrusion and granulation by heating the barrel and screw shearing, the nylon material is obtained.

9. The preparation method according to claim 8, characterized in that: The processing temperature of the twin-screw extruder is controlled at 210-250° C., and the main engine speed is 300-350 rpm.